Metabolic Effects of Insulin and IGFs on Gilthead Sea Bream (Sparus aurata) Muscle Cells - Montserrat, Núria; Capilla, Encarnación; Navarro, Isabel; Gutiérrez, Joaquim (Frontiers in Endocrinology, 2012)
Primary cultures of gilthead sea bream myocytes were performed in order to examine the relative metabolic function of insulin compared with IGF-I and IGF-II (IGFs) at different stages in the cell culture. In these cells, the in vitro effects of insulin and IGFs on 2-deoxyglucose (2-DG) and L-alanine uptake were studied in both myocytes (day 4) and small myotubes (day 9). 2-DG uptake in gilthead sea bream muscle cells was increased in the presence of insulin and IGFs in a time dependent manner and along with muscle cell differentiation. On the contrary, L-alanine uptake was also stimulated by insulin and IGFs but showed an inverse pattern, being the uptake higher in small myocytes than in large myotubes. The results of preincubation with inhibitors (PD-98059, wortmannin and citochalasin B) on 2-DG uptake indicated that insulin and IGFs stimulate glucose uptake through the same mechanisms, and evidenced that MAPK and PI3K-Akt transduction pathways mediate the metabolic function of these peptides. In the same way, we observed that GLUT4 protein synthesis was stimulated in the presence of insulin and IGFs in gilthead sea bream muscle cells in a different manner at days 4 or 9 of the culture. In summary we describe here, for the first time, the effects of insulin and IGFs on 2-DG and L-alanine uptake in primary culture of gilthead sea bream muscle cells. We show that both MAPK and PI3K-Akt transduction pathways are needed in order to control insulin and IGFs actions in these cells. Moreover, changes in glucose uptake can be explained by the action of the GLUT4 transporter, which is stimulated in the presence of insulin and IGFs throughout the cell culture.